SpinachBase: a central portal for spinach genomics. (18th June 2019) - Collins, Keeley; Zhao, Kun; Jiao, Chen; Xu, Chenxi; Cai, Xiaofeng; Wang, Xiaoli; Ge, Chenhui; Dai, Shaojun; Wang, Quanxi; Wang, Quanhua; Fei, Zhangjun; Zheng, Yi
Abstract: Spinach ( Spinacia oleracea L.) is a nutritious vegetable enriched with many essential minerals and vitamins. A reference spinach genome has been recently released, and additional spinach genomic resources are being rapidly developed. Therefore, there is an urgent need of a central database to store, query, analyze and integrate various resources of spinach genomic data. To this end, we developed SpinachBase (http://spinachbase.org ), which provides centralized public accesses to genomic data as well as analytical tools to assist research and breeding in spinach. The database currently stores the spinach reference genome sequence, and sequences and comprehensive functional annotations of protein-coding genes predicted from the genome. The database also contains gene expression profiles derived from RNA-Seq experiments as well as highly co-expressed genes and genetic variants called from transcriptome sequences of 120 cultivated and wild Spinacia accessions. Biochemical pathways have been predicted from spinach protein-coding genes and are available through a pathway database (SpinachCyc) within SpinachBase. SpinachBase provides a suite of analysis and visualization tools including a genome browser, sequence similarity searches with BLAST, functional enrichment and functional classification analyses and functions to query and retrieve gene sequences and annotations.